Scutellaria radix Extract as a Natural UV Protectant for Human Skin. (1st December 2015) - Seok, Jin Kyung; Kwak, Jun Yup; Choi, Go Woon; An, Sang Mi; Kwak, Jae‐Hoon; Seo, Hyeong‐Ho; Suh, Hwa‐Jin; Boo, Yong Chool
Abstract : Ultraviolet (UV) radiation induces oxidative injury and inflammation in human skin. Scutellaria radix (SR, the root of Scutellaria baicalensis Georgi) contains flavonoids with high UV absorptivity and antioxidant properties. The purpose of this study was to examine the potential use of SR extract as an additive in cosmetic products for UV protection. SR extract and its butanol (BuOH) fraction strongly absorbed UV radiation and displayed free radical scavenging activity against 2, 2‐diphenyl‐1‐picrylhydrazyl radials and 2, 2′‐azinobis‐(3‐ethylbenzothiazoline‐6‐sulfonic acid) radicals. They also attenuated the UV‐induced death of HaCaT cells. Sunscreen creams, with or without supplementation of SR extract BuOH fraction, were tested in vivo in human trials to evaluate potential skin irritation and determine the sun protection factor (SPF). Both sunscreen creams induced no skin irritation. A sunscreen cream containing 24% ZnO showed an SPF value of 17.8, and it increased to 22.7 when supplemented with 5% SR extract BuOH fraction. This study suggests that SR‐derived materials are useful as safe cosmetic additives that provide UV protection. Copyright © 2015 John Wiley & Sons, Ltd.